Restorative Justice Tindak Pidana Kekerasan Pada Anak Sebagai Korban (Studi Komparatif Hukum Pidana Positif dan Hukum Pidana Islam) - Wahyuda, Agung Taufik; Suparmin, Sudirman (Nagari Law Review, 2025)
The resolution of criminal cases constantly evolves in line with criminal justice theory. One development in criminal justice theory is the development of criminal justice, which aims not to be punitive but to address the situation through out-of-court settlements, such as restorative justice mechanisms. However, Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence states that cases of sexual violence cannot be resolved outside the judicial process, except for child perpetrators. Meanwhile, the application of restorative justice has been expanded to include crimes whose perpetrator is an adult that are not settled in the juvenile criminal justice system. Therefore, this study analyzes the application of restorative justice in cases of sexual violence against child victims. The research was a normative legal research that was conducted by comparing Indonesian positive and Islamic criminal law. The study employed a normative method through a statutory and comparative legal approach. The results of the study indicate that resolving sexual violence cases outside the courts, such as through restorative justice, does not allow for resolution. This regulation provides more legal certainty and has a greater deterrent effect. Conversely, in Islamic criminal law, non-penetrative sexual violence is categorized as a taʿzir crime that does not have rigid punishment provisions, thus providing judges with flexibility to impose contextual sanctions. This system allows for applying a restorative justice approach, as long as the victim's rights are maintained. It is recommended that national criminal law consider legal reforms that recognize the existence of categories of sexual violence with different levels of risk, so that it remains possible for crimes of sexual violence with specific qualifications to be resolved through restorative justice.